On one way of installing electric machine brushes on the geometrical neutral - Попов, М. П. (Proceedings of National Aviation University (archive), 1998)
Considered is one way of simplifying the process of installation of brushes of direct current electric machines on the line of geometric neutral. Explained are the principles of the proposed way and given experimental data, confirming its efficiency